Changes in Corneal Higher-Order Aberrations and Ocular Biometric Measurements after Phacoemulsification Combined with Goniosynechialysis in Primary Angle Closure/Glaucoma Patients - Jiali Xia; Siqi Guo; Fei Hu; Liqi Fan; Ling Yu; Jian Ye (Journal of Ophthalmology)
Purpose. To compare corneal higher-order aberrations (HOAs), refractive error, and ocular biological parameters before and after phacoemulsification combined with goniosynechialysis (Phaco-GSL) in primary angle closure/glaucoma (PAC/PACG) patients with different axial lengths (ALs). Methods. In this prospective study, cataract patients diagnosed with PAC/PACG were categorized into two groups based on their ALs: the short AL group (AL ≤ 22.5 mm) and the normal AL group (22.5 < AL ≤ 24.5 mm). The pre- and postsurgery measurements of intraocular pressure (IOP) and best-corrected visual acuity (BCVA) were conducted at 1 day, 1 week, 1 month, 3 months, 6 months, and 12 months. Additionally, the assessments included corneal HOAs, the number of antiglaucoma medications, visual field parameters, manifest refraction, and other ocular biological parameters before surgery and at the final follow-up. Results. Prior to surgery, the two groups exhibited no significant differences, except for AL, curvature value, and Z (4, 0) of the posterior corneal surface (all P<0.01). Following surgery, BCVA improved, and IOP decreased significantly in both groups (P<0.01). Both anterior and total corneal HOAs, along with Z (3, −3), increased in the two groups (all P<0.05), with the normal AL group exhibiting a significantly greater increase in total cornea Z (3, −3) than the short AL group (P=0.047). The normal AL group also exhibited a slight tendency towards hyperopia (P<0.01). Significant changes were observed in the visual field index and mean deviation in both groups (P<0.05). Conclusions. Phaco-GSL resulted in an increased corneal HOAs, particularly trefoil, with variations based on the patient’s AL. Patients with normal ALs tended to shift towards hyperopia after surgery.